CORRELATION BETWEEN LIVER FUNCTIONAL PARAMETERS AND DISORDERS OF PORTOLIVER CIRCULATION OF BLOOD AND LYMPHOKINESIS IN CHILDREN WITH CIRRHOSIS - A.A. Gafurov; V.V. Botvin'eva; M.M. Aliev ("Paediatrician" Publishers LLC, 2008)
.